As sacred to us : Simon Pokagon's birch bark stories in their contexts - Morseau, Blaire (Michigan State University Press, 2023)
"Originally published in 1893 and 1901, Simon Pokagon's birch bark stories were printed on thinly peeled and elegantly bound birch bark. These booklets are reprinted with new essays that set the stories in cultural, linguistic, historical, and even geological context. Experts in Native literary traditions, history, Algonquian languages, the Michigan landscape, and materials conservation illuminate the thousands of years of Indigenous knowledge that Pokagon elevated in his stories"-- Provided by publisher.
Description based upon print version of record.
Keywords: Pokagon, Simon, -- 1830-1899 -- Criticism and interpretation.; Pokagon, Simon, -- 1830-1899; American literature -- Indian authors -- History and criticism.; Potawatomi literature -- Michigan -- History and criticism.; Pokagon, Simon, 1830-1899--Criticism and interpretation.; Potawatomi literature--Michigan--History and criticism.; American literature--Indian authors--History and criticism.; Littérature américaine -- Auteurs indiens d'Amérique -- Histoire et critique.; American literature -- Indian authors; Michigan; LITERARY COLLECTIONS / General; Criticism, interpretation, etc.